(3GdSdhc deYQaI Ohd Gdedhcs - (3CMeO Hf Ydj Hf YHO GdbGOQ, CHh GdYHGS GdMSjfj GdYHjOj, Jbj GdOjf GdebQjRj,J (B845 (3g` s
(3ChdgG (B:s
(3jHJOF HSfI (B811 s
(3BNQgG (B:s
(3jfJgi HSfI (B844 (3hcJH ai BNQgG(B: (3hHg Je GdcJGH HhaGI eDdag QMeg Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B11s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B39 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B155 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1000s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs